Berättelsens och framförandets olika världar - Öhman, Sara (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
In this article I combine the models of Katharine Young, William Labov, Gillian Bennett to analyse Anna’s, a Visby pensioner, story about an event that had great impact on her life — while in Uppsala to study, she fell ill with polio. By observing the narrator’s and the narrative’s movements between taleworld, storyrealm and the realm of conversation, while at the same time paying attention to both intra-narrative and communicative aspects, it became obvious to me that inside Young’s three worlds, we are also able to recognize enclaves of metacommunicative quality. These enclaves are characterised by explanatory, evaluative, and credibility creating functions. As metacommunicative signals they constitute part of the interplay between narrator and listener, facilitating the audience’s proper interpretation of the narrator’s coding of her telling.